A customized anthropomorphic 3D-printed phantom to reproducibility assessment in computed tomography: an oncological case study - Cavaliere, Carlo; Baldi, Dario; Brancato, Valentina; Aiello, Marco; Salvatore, Marco (Frontiers in Oncology, 2023)
Studies on CT reproducibility at different acquisition parameters have to take into account radiation dose administered and related ethical issues. 3D printed phantoms provide the possibility to investigate these features deeply and to foster CT research, also taking advantage by outperforming new generation scanners. Aim of this study is to propose a new anthropomorphic 3D-printed phantom for chest lesions, tailored on a real patient CT scan, to investigate the variability of volume and densityHounsfield Unit (HU) measurements at different CT acquisition parameters. The chest CT of a 75-year-old patient with a paramediastinic lung lesion was segmented based on an 8-compartment approach related to HU ranges (air lung, lung interstitium, fat, muscle, vascular, skin, bone, and lesion). From each mask produced, the 3D .stl model was exported and linked to a different printing infill value, based on a preliminary test and HU ratios derived from the patient scan. Fused deposition modeling (FDM) technology printing was chosen with filament materials in polylactic acid (PLA). Phantom was acquired at 50 mAs and three different tube voltages of 80 kVp, 100 kVp, and 120 kVp on two different scanners, namely Siemens Somatom Force (Siemens Healthineers, Erlangen, Germany; same setting of real patient for 80kVp acquisition) and GE 750 HD CT (GE Healthcare, Chicago, IL). The same segmentation workflow was then applied on each phantom acquisition after coregistration pipeline, and Dice Similarity Coefficient (DSC) and HU averages were extracted and compared for each compartment. DSC comparison among real patient vs. phantom scans at different kVp, and on both CT scanners, demonstrated a good overlap of different compartments and lesion vascularization with a higher similarity for lung and lesion masks for each setting (about 0.9 and 0.8, respectively). Although mean HU was not comparable with real data, due to the PLA material, the proportion of intensity values for each compartment remains respected. The proposed approach demonstrated the reliability of 3D-printed technology for personalized approaches in CT research, opening to the application of the same workflow to other oncological fields.The overall methodological workflow of the proposed approach is shown inFigure 1.Formatted: Highlight